2007
DOI: 10.1007/s00221-007-1243-2
|View full text |Cite
|
Sign up to set email alerts
|

Distractor effects on saccade trajectories: a comparison of prosaccades, antisaccades, and memory-guided saccades

Abstract: The present study investigated the contribution of the presence of a visual signal at the saccade goal on saccade trajectory deviations and measured distractor-related inhibition as indicated by deviation away from an irrelevant distractor. Performance in a prosaccade task where a visual target was present at the saccade goal was compared to performance in an anti-and memory-guided saccade task. In the latter two tasks no visual signal is present at the location of the saccade goal. It was hypothesized that if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 53 publications
(62 reference statements)
0
10
1
Order By: Relevance
“…While our results show that strengthening the target signal with a coincident tone can lead to an increase in deviations away from distractors, a recent study by van Zoest et al (2008) found the opposite effect; weaker deviations away for stronger target signals. In that study, when the strength of the stimulus-driven target signal was increased by presenting a visual stimulus at the target location (rather than having participants perform antisaccades or memory-guided saccades), deviations away from distractors were reduced.…”
Section: Discussioncontrasting
confidence: 95%
“…While our results show that strengthening the target signal with a coincident tone can lead to an increase in deviations away from distractors, a recent study by van Zoest et al (2008) found the opposite effect; weaker deviations away for stronger target signals. In that study, when the strength of the stimulus-driven target signal was increased by presenting a visual stimulus at the target location (rather than having participants perform antisaccades or memory-guided saccades), deviations away from distractors were reduced.…”
Section: Discussioncontrasting
confidence: 95%
“…This criterion was selected for two reasons. First, in experimental blocks with antisaccades alone, the mean response latency is around 250 ms-for example, Evdokimidis et al (1996), Weber et al (1998), andVan Zoest et al (2008): hence, using this will give us reasonably equivalent numbers of short-and long-latency antisaccades. Second, experiments using multiple stimuli or simultaneous distractors show that spatial biases are more evident in saccades with latencies \250 ms (Van Zoest et al 2004; Van der Stigchel and Theeuwes 2005).…”
Section: Discussionmentioning
confidence: 99%
“…42 , reported that deviations away from a distractor were observed for longest latencies and deviations towards a distractor in case of shorter latencies with the transition point around latency of 200 ms. The same, however, does not hold for anti-saccades and longest latencies did not correspond to greatest distractor caused deviations 43 . Saccadic deviations are also influenced by the distance of the distractor to the target 44,45 , vertical distance of the distractor from the fixation 46 and the target hemifield 47 .…”
Section: Alternative Measures Of Attention Deploymentmentioning
confidence: 90%